PENINGKATAN NILAI TAMBAH PRODUK OLAHAN SUSU BUBUK DI âUMKM ETAWA AGRO PRIMA TURIâ DENGAN PENERAPAN AUDIT PRODUKSI BERSIH - , FAHMI PRAMUDYA; , Dr. Wagiman, STP., M.Si, ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The use of raw materials, energy, and waste management are critical success factors of an industry. Cleaner production is an activity to minimize the use of resources in an industrial raw material. MSME Etawa Agro Prima food industry is one that has the potential to implement cleaner production. This study aimed to generate cleaner production option scheme as a solution in milk processing Etawa. Cleaner production audit method is applied to reduce energy and water usage in an industry. Pre-evaluation is conducted to obtain data on the amount of energy and water consumption, and waste management. Evaluation was conducted to determine the potential of cleaner production that can be applied. Cleaner production schemes and the selection is done to choose the right cleaner production scheme to be applied. Feasibility analysis includes technical feasibility, economic, and environmental. Implementation of the scheme was to increase the production of clean energy and water usage decreased production process. The results showed the level of energy consumption of gas, water, and electricity can be minimized up to 55.5%, 66.7%, and 5.07% respectively, compared to before the cleaner production audit. Results Etawa goat milk powder production can be increased up to 5.01% compared to the prior audit applied cleaner production.